Solvent extraction reaction of uranium (VI) sulfate with Alamine 336 - Avelar, Erica; Resende, G.P.S.; Mansur, M.B. (2014)
The solvent extraction equilibrium reaction of uranium (VI) sulfate with Alamine 336 as an extractant dissolved in Exxsol D-100 and 5% v/v tridecanol as a modifying agent at room temperature (25±2)⁰C has been investigated. Experimental data at typical concentration levels like those used at the uranuium plant of Caetie, Brazil, obtained by Alvarenga (2010) were used. Data fitting using the slope analysis method revealed that uranium is preferentially extracted by Alamine 336 as UO₂SO₄ species, but extraction of UO₂(SO₄)₂²⁻ species may also occur simultaneously.